FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PELAKSANAAN INISIASI MENYUSU DINI (IMD) PADA IBU BERSALIN DI RSUD KOTA PRABUMULIH (Program Studi Ilmu Kesehatan STIKES Abdi Nusa Pangkalpinang, 2022)
ABSTRACTEarly breastfeeding initiation is the process of putting a newborn baby on the mother's chest or stomach so that the baby can naturally find its own source of breast milk or breast milk and start breastfeeding the baby will get immunity. The purpose of this study was to determine the factors associated with the implementation of early breastfeeding initiation (IMD) in the City Hospital of Prabumulih. The method of the research was analytic study with cross sectional approach. The population in this study were all women giving birth at Prabumulih City Hospital. The research sample was the majority of women giving birth at the City Hospital in Prabumulih in 2020 with a total of 35 peopl e. The instrument used was a questionnaire as a guide for data collection. The analysis used is univariate and bivariate analysis. The results of the study based on univariate analysis revealed that of the 35 respondents obtained by respondents who did Early Breastfeeding Initiation as many as 20 respondents (57.1%) more than those who did not do Early Breastfeeding Initiation as many as 15 respondents (42.9%), from 35 respondents found that respondents who had higher education as many as 19 respondents (54.3%) more than respondents with low education as many as 16 respondents (45.7%), from 35 respondents found that respondents with number of children ≥ 3 were 9 respondents (25.7%) less than respondents with number of children ≤ 2 as many 26 respondents (74. 3%), and from 35 respondents found that those with good knowledge were 19 respondents (54.3%) more than respondents with low knowledge as many as 16 respondents (45.7%). From the bivariate analysis it is known that there is a significant relationship between maternal education with Early Breastfeeding I nitiation p value = 0,000 (p< 0,05 ), there is a significant relationship between maternal parity with Early Breastfeeding Initiation with p value = 0,002 (p< 0,05 ), and there is a relationship meaningful between mother's knowledge with Early Breastfeeding Initiation with p value = 0,000 (p< 0,05 ).